Systemic Blood Predictors of Elevated Pulmonary Artery Pressure Assessed by Non-invasive Echocardiography After Acute Exposure to High Altitude: A Prospective Cohort Study - Bian, Shi-Zhu; Zhang, Chen; Rao, Rong-Sheng; Ding, Xiao-Han; Huang, Lan (Frontiers in Cardiovascular Medicine, 2022)
Aim Elevated pulmonary artery pressure (ePAP) in response to high-altitude hypoxia is a critical physiopathological factor in the hypoxic adaptation that may lead to high-altitude pulmonary edema in the acute phase or high-altitude pulmonary hypertension in the long term. However, the sea-level predictors of risk factors for altitude-induced ePAP have not been examined. Thus, we aimed to identify the baseline systemic blood predictors of ePAP after acute high-altitude exposure. Materials and Methods A total of 154 participants were transported to a high altitude 3,700 m from sea level within 2 h. Echocardiography examinations were performed to assess the mean pulmonary artery pressure (mPAP) and hemodynamics at both altitudes. All the individuals underwent blood tests to determine the concentrations of vascular regulatory factors. Univariate and adjusted logistic regression analyses were performed to identify the independent predictors of ePAP and factors related to ePAP. Results The mPAP increased significantly from sea level to high altitude (19.79 ± 6.53–27.16 ± 7.16 mmHg, p < 0.05). Increased levels of endothelin (ET-1), Ang (1–7), Ang II, and bradykinin were found after high-altitude exposure, while the levels of nitric oxide (NO), prostaglandin E2 (PEG2), and serotonin decreased sharply (all p-values < 0.05). At high altitude, 52.6% of the subjects exhibited ePAP, and the mPAP was closely correlated with the baseline Ang II level (r = 0.170, p = 0.036) and follow-up levels of NO (r = −0.209, p = 0.009), Ang II (r = 0.246, p = 0.002), and Ang (1–7) (r = −0.222, p = 0.006) and the left atrial inner diameter (LAD, r = 0.270, p < 0.001). Both the baseline and follow-up NO and Ang II levels were significantly different between the ePAP and non-ePAP groups. Finally, we identified the baseline Ang II and NO concentrations as two independent predictors of ePAP (p < 0.05). We also found that two vascular regulatory factors with inverse roles, namely, Ang (1–7) and Ang II, at high altitudes were independently associated with ePAP. Additionally, ET-1, NO, PEG2, and LAD were associated with ePAP. Conclusion The baseline concentrations of Ang II and NO at sea level are two independent predictors of ePAP after acute high-altitude exposure. Furthermore, Ang (1-7) and Ang II combined with ET-1, NO, PEG2, and LAD at high altitudes may contribute to the development of ePAP.